Concurrent material selection of natural fibre filament for fused deposition modeling using integration of analytic hierarchy process/analytic network process - Mohammad Taha, Mastura; Siti Azura, Ahmad Tarusan; Abdul Kudus, Syahibudil Ikhwan; Hussin, Mohamed Saiful Firdaus; Razali, Nadlene; Mansor, Muhd Ridzuan (Tech Science Press, 2022)
The employment of natural fibres in fused deposition modeling has raised much attention from researchers in finding a suitable formulation for the natural fibre composite filaments. Moreover, selection of suitable natural fibres for fused deposition modeling should be performed before the development of the composites. It could not be performed without identifying selection criteria that comprehend both materials and fused deposition modeling process requirements. Therefore, in this study, integration of the Analytic Hierarchy Process (AHP)/ Analytic Network Process (ANP) has been introduced in selecting the natural fibres based in different clusters of selection concurrently. The selection process has been performed based on the interdependency among the selection criteria. Pairwise comparison matrices are constructed based on AHP’s hierarchical model and super matrices are constructed based on the ANP’s network model. As a result, flax fibre has ranked at the top of the selection by scored 19.5% from the overall evaluation. Flax fibre has excellent material properties and been found in various natural fibre composite applications. Further investigation is needed to study the compatibility of this fibre to be reinforced with a thermoplastic polymer matrix to develop a resultant natural fibre composite filament for fused deposition modeling.